2022
DOI: 10.1002/asl.1139
|View full text |Cite
|
Sign up to set email alerts
|

The roles of atmospheric circulation and sea surface temperature in UK surface climate

Abstract: Atmospheric circulation has been identified as a key driver of recent extreme seasons in the UK, while local sea surface temperature (SST) also influences UK surface climate. Here, we investigate the roles of atmospheric circulation and SST in driving UK climate, using atmospheric model simulations with constrained global atmospheric circulation and selected SST boundary conditions. These simulations successfully reproduce observed UK-mean temperature and precipitation. For UK temperature, circulation has a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
(66 reference statements)
2
1
0
Order By: Relevance
“…For monthly means, reconstructed England temperatures show average correlations with the model temperatures of 0.73, 0.70, and 0.66 for June, July and August, with precipitation correlations in the range 0.8–0.9 for all DJF‐MAM‐JJA months. A substantial proportion of England temperature and precipitation variance is therefore circulation‐related, consistent with Fereday and Knight (2022).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…For monthly means, reconstructed England temperatures show average correlations with the model temperatures of 0.73, 0.70, and 0.66 for June, July and August, with precipitation correlations in the range 0.8–0.9 for all DJF‐MAM‐JJA months. A substantial proportion of England temperature and precipitation variance is therefore circulation‐related, consistent with Fereday and Knight (2022).…”
Section: Resultssupporting
confidence: 81%
“…Conversely, circulation contributes to dry DJF-MAM-JJA throughout, with almost all extreme dry seasons in the lowest 25% of circulation-related precipitation. This is again consistent with Fereday and Knight (2022), who found that historical UK precipitation is strongly driven by atmospheric circulation. Unlike temperature, there is little trend in DJF-MAM-JJA precipitation, with wetter winters balancing drier summers.…”
Section: Analysis Linking Hot and Dry Conditions With Atmospheric Cir...supporting
confidence: 92%
See 1 more Smart Citation